Synaptic Stress and Pathogenesis of Neuropsychiatric Disorders - Popoli, Maurizio.; Popoli, Maurizio.; Diamond, David.; Diamond, David.; Sanacora, Gerard.; Sanacora, Gerard. (Springer New York : Imprint: Springer, 2014)
An overview of the ways in which stress affects brain function or synaptic plasticity and can precipitate the onset of neuropsychiatric disorders. Recent research has shown that changes in glutamate/GABA synapses and related pathways are involved in determining whether the effects of a particular stressor will be adaptive or maladaptive. Among the topics discussed are the impact of behavioral stress and glucocorticoids on tripartite glutamate synapses and synaptic transmission, the way that psychiatric drugs affect these same mechanisms, and how the molecular/cellular/functional effects of stress may trigger disorders such as depression, schizophrenia, anxiety, and PTSD. The results presented have been obtained through a range of different and complementary methods including live imaging, electrophysiology, glutamate release from isolated live synaptic terminals, transgenic and animal models, and new behavioral methods.